Determinants of Nordic Entrepreneurship: A Reverse Engineered Pitch - Ondřej Dvouletý (Journal of Accounting and Management Information Systems (JAMIS), 2017)
Faff (2015; 2017) has introduced a very useful pitching research template for understanding academic literature and for formation of research ideas and concepts. This pitching research letter (PRL) applies Faffs (2015; 2017) template to the example of a "reverse engineering" pitch in the field of entrepreneurship. I share the positive experience of Salehudin (2017) who applied pitching research template on an already published study. In my case, the pitching research template is applied on the article written by Dvouletý (2017), which focuses on the determinants of Nordic entrepreneurship. The letter offers a personal reflection on the application of the pitching research template. Finally, it highlights the need to increase visibility of my own research.
Keywords: M2; M1; L26; Y20; 650; Pitching Research Letter; Reverse Engineering Pitch; Nordic Entrepreneurship; Necessity Entrepreneurship; Entrepreneurial Economics